Etnometodologia e discurso instrucional: elementos teórico-metodológicos para a pesquisa de sala de aula - Silva Neto, João Gomes da (2002)
This work aims to reflect on the elaboration of a theoretical and methodological model of applied linguistics, focusing on the classroom speech. This paper has been elaborated throughout a research based on ethnomethodology, gathering other approaches such as conversation analysis, socio-linguistics and pragmatics.